Analisis Praktik Manajemen Kepegawaian Di Lingkungan Universitas Bengkulu (Studi Pada Aparatur Sipil Negara Tenaga Kependidikan/Karyawan) - Sari Simanungkalit; Slamet Widodo; I Wayan Dharmayana (The Manager Review, 2022)
Abstract This study aims to describe the practice of personnel management at the University of Bengkulu which is seen from the aspects of the preparation and determination of government apparatus, procurement of government apparatus, government apparatus ranks and positions, career development, allowances and salaries and the application of discipline. This type of research uses a qualitative approach with survey methods. In this study, the authors collected information data and basic information by using a distributed questionnaire. The data that will be used in this study is primary data obtained directly from respondents, namely government apparatus in Bengkulu University. Research respondents amounted to 296 people or 93.4% of the total education staff at Bengkulu University. The data analysis method used descriptive analysis and qualitative analysis. The results of the study indicate that (1) the preparation and determination of needs in the management of government apparatus at Bengkulu University has been arranged adequately; (2) Procurement is in the category according to need. In the procurement of government apparatus, Bengkulu University's personnel management carried out adequate planning; (3) In the implementation of the next government apparatus management, management of government apparatus ranks and positions is carried out; (4) The dimensions of career development in government apparatus management at Bengkulu University have been carried out in accordance with applicable regulations; (5) The response to the assessment of government apparatus performance in the implementation of government apparatus management is in accordance with applicable regulations; (6) Salaries and allowances for government apparatus at Bengkulu University have been carried out in accordance with applicable regulations; and (7) employee discipline within the Bengkulu University is in the appropriate category. Keywords: Preparation and Determination, Procurement, Rank and Position, Career Development, Allowances and Payroll, and Application of Discipline Abstrak: Penelitian ini bertujuan untuk mendeskripsikan praktik manajemen kepegawaian di Universitas Bengkulu yang dilihat dari aspek penyiapan dan penetapan aparatur pemerintah, pengadaan aparatur pemerintah, pangkat dan jabatan aparatur pemerintah, pengembangan karir, tunjangan dan gaji serta penerapannya. disiplin. Jenis penelitian ini menggunakan pendekatan kualitatif dengan metode survei. Dalam penelitian ini, penulis mengumpulkan data informasi dan informasi dasar dengan menggunakan kuesioner yang disebarkan. Data yang akan digunakan dalam penelitian ini adalah data primer yang diperoleh langsung dari responden yaitu aparatur pemerintah di Universitas Bengkulu. Responden penelitian berjumlah 296 orang atau 93,4% dari total tenaga kependidikan Universitas Bengkulu. Metode analisis data menggunakan analisis deskriptif dan analisis kualitatif. Hasil penelitian menunjukkan bahwa (1) persiapan dan penetapan kebutuhan dalam penyelenggaraan aparatur pemerintahan di Universitas Bengkulu sudah tertata dengan baik; (2) Pengadaan dalam kategori sesuai kebutuhan. Dalam pengadaan aparatur pemerintah, manajemen kepegawaian Universitas Bengkulu melakukan perencanaan yang memadai; (3) Dalam penyelenggaraan pemerintahan aparatur pemerintahan selanjutnya dilakukan pengurusan kepangkatan dan jabatan aparatur pemerintahan; (4) Dimensi pengembangan karir pada manajemen aparatur pemerintah di Universitas Bengkulu telah dilaksanakan sesuai ketentuan yang berlaku; (5) Respon terhadap penilaian kinerja aparatur pemerintah dalam penyelenggaraan manajemen aparatur pemerintah sesuai dengan ketentuan yang berlaku; (6) Gaji dan tunjangan aparatur pemerintah di lingkungan Universitas Bengkulu telah dilaksanakan sesuai ketentuan yang berlaku; dan (7) disiplin pegawai di lingkungan Universitas Bengkulu termasuk dalam kategori sesuai. Kata Kunci : Persiapan dan Penetapan, Pengadaan, Pangkat dan Jabatan, Pengembangan Karir, Tunjangan dan Penggajian, dan Penerapan Disiplin